Data Interpretation in Anesthesia : A Clinical Guide - Raj, Tilak D. (Springer International Publishing : Imprint: Springer, 2017)
Focusing on the interpretation of data commonly available to anesthesiologists, this book presents a data point, followed by discussion in a question and answer format. Covering EKG's, X-Rays, MRI's, graphs, paper recordings, blood gas results, laboratory results, patient case histories and more, Data Interpretation in Anesthesia provides an enhanced and stimulating learning format for residents in training and practitioners alike.
Keywords: Medicine.; Anesthesiology.; elektronické knihy; electronic books